Chapter I viaggi europei di Ljubomir Nenadović - Banjanin, Ljiljana (Biblioteca di Studi Slavistici, 2019)
This article examines travel letters that Ljubomir Nenadović (1826-1895) wrote from Switzerland (1847), Italy (1850-1851) and Germany (1870). Marking three different phases in the literary biography of their author, these texts provide evidence of the travel letter's polyphonic nature. We argue that the dynamic shape and narrative texture of Nenadović's letters find their source in the nature of the differences that he observes and identifies, differences that distinguish these countries from his Serbian homeland and, more generally, from the cultural and geographic space of the Slavs.